Jean Baudrillard and Terrorism - Codeluppi, Vanni (Italian Sociological Review, 2017)
The main purpose of this article is to consider the role attributed to terrorism by the French sociologist Jean Baudrillard, who conducted an extensive study on the nature of terrorism in the West over the course of three decades. His enquiry started with an analysis of the relationship between terrorism and the media, and led to the development of a number of concepts that will be considered in detail in this article. These concepts share the idea that in the West we are currently witnessing a return to what Baudrillard defined as the ‘symbolic exchange’, a concept which draws on the French tradition of sociological and anthropological research.